Pengaruh Mata Kuliah Kewirausahaan, Praktek Kewirausahaan, Self Efficacy terhadap Minat Berwirausaha Mahasiswa Universitas Jambi - Fitriyansyah, Mitha; Harmanda, Debby; Pratama, Sari; Septianti, Amanda; Pratami, Avitri Vita; Marsela, Marsela (Indonesian Educational Administration and Leadership Journal (IDEAL), 2021)
The purpose of this study was to find out 1) The effect of entrepreneurship courses on the interest in entrepreneurship at Jambi University students; 2) The effect of entrepreneurial practice on the interest in entrepreneurship at Jambi University students; 3) The effect of self-efficacy on the interest in entrepreneurship at Jambi University students. This research is quantitative descriptive. The population in this study were all Jambi university students. The sampling technique in this study used a purposive sampling technique. The sample in this study were Jambi university students, namely 207 respondents. The data collection technique used is a questionnaire technique. The data analysis used is SEM-PLS analysis. The results of this study indicate that the entrepreneurship course has a positive effect on the interest in entrepreneurship at Jambi University students, the entrepreneurship course has a positive and significant effect on the entrepreneurial practices of Jambi University students, self-efficacy has a positive and significant effect on the interest in entrepreneurship at Jambi University students, and self-efficacy also has a positive effect. and significant to the entrepreneurial practices of Jambi university students while entrepreneurial practices did not have a significant effect on the interest in entrepreneurship of Jambi university students. Kata Kunci : Entrepreneurship courses, Entrepreneurial practice, Self-efficacy , Interest in entrepreneurship